ANALISIS PENGEMBANGAN POTENSI EKONOMI PARIWSATA RELIGI DI MASJID JAMI TEGALASARI PONOROGO - Nijla Shifyamal Ulya; Faruq Ahmad Futaqi (Niqosiya: Journal of Economics and Business Research, 2022)
Religious tourism as a sector that focuses on Muslim tourists whose implementation is in accordance with sharia principles. The development of sharia tourism, especially economic pontential, needs to be done to improve people’s welfare and increase income. Background Problems: The existence of a religious tourism object at the Jami Tegalsari mosque in Ponorogo indirectly plays a role in the welfare of the community to increase income. All tourism development activities are carried out by the village government and managers to provide satisfaction to tourism and bussiness actors who are around the religious tourism object of the jami Tegalsari mosque. Novelty: This research was conducted in Tegalsari Ponorogo, there has been no similar researchers discussing the same theme. Data collections techniques used include observation, interview, and documentation. Interviews were coducted with several element, namely mr. Khairul Huda as the village head of Tegalsari, mr. Hamdan Rifa’i as the ta’mir of the jami Tegalsari mosque, and mrs Puji Rahayu, one of the traders who was in the area of the jami Tegalsari mosque. Meanwhile the data analysis obtained by the researcheris data reduction and data presentation. Methods: The method used in this reseacrh is descriptive qualitative method. Finding/ Results: The Results of the study show that the development of religious tourism includes the construction of shop houses, repair of tombs, expansions of the hall, management by POKDARWIS, expansion of parking areas. Efforts made in this tourism development include publications, promotions related to toeurism development activities, structuring street vendors, parking, improving the quality of human resources, collaborating with relevant agencies and agencies that are aware of religious tourism development activities, building bridges between Tegalsari villages and hamlests. Setono the grave of Mbah Donopuro, carried out the development of the tomb of Mbah Donopuro, Prince Semende. The factors behind thedevelopment are socio-cultural fators, namely ancestral culture that needs to be preserved, economic factors to improve people’s quality of life, and religious factors which are the forerunners of Indonesian Islamic boarding scholls. Conclusion: the conclusion that can be drawn from this research is that this researchs gives very good results, seen from the direct involvemnt of village goverment, ta’mir, and also the surrounding community. The existence of this development can increase the income of people who trade around tourism objects. Keywords: Development, Economic Potential, Religious Tourism Abstrak: Pariwisata religi sebagai salah satu sektor pariwisata yang terfokus pada wisatawan muslim yang pelaksanaannya sesuai prinsip syariah. Pengembangan wisata syariah khususnya potensi ekonomi perlu dilakukan untuk meningkatkan kesejahteraan masyarakat dan meningkatkan pendapatan. Adanya obyek wisata religi masjid jami Tegalsari ponorogo secara tidak langsung berperan dalam kesejahteraan masyarakat untuk meningkatkan pendapatan. Semua kegiatan pengembangan pariwisata dilakukan pemerintah desa beserta pengelola untuk memberikan kepuasan kepada wisatawan dan pelaku usaha yang berada di sekitar obyek wisata religi masjid Jami Tegalsari. penelitian ini dilakukan di Tegalsari Ponorogo, belum adanya penelitian yang sama yang dilakukan oleh peneliti lain yang membahas tema yang sama. Metode yang digunakan dalam penelitian ini yaitu menggunakan metode kualitatif deskriptif. Teknik pengumpulan data yang digunakan diantaranya observasi, wawancara, serta dokumentasi. Wawancara dilakukan dengan beberapa elemen yakni bapak Khoirul Huda selaku kepala desa Tegalsari, bapak Hamdan Rifa’i selaku ta’mir masjid jami Tegalsari, dan ibu Puji Rahayu salah satu pedagang yang berada di area masjid jami Tegalsari. Sedangkan analisa data yang diperoleh peneliti yakni reduksi data dan penyajian data. Hasil penelitian menunjukkan wujud pengembangan pariwisata religi mencakup pembangunan ruko, perbaikan makam, perluasan aula, pengelolaan oleh POKDARWIS, perluasan lahan parkir. Upaya yang dilakukan dalam pengembangan wisata ini mencakup publikasi, promosi terkait dengan kegiatan pengembangan wisata, melakukan penataan PKL, parkir, meningkatkan kualitas SDM, bekerja sama dengan dinas terkait maupun instansi yang sadar akan kegiatan pengembangan wisata religi, membangun jembatan penghubung antara desa Tegalsari dengan dukuh Setono makam Mbah Donopuro, melakukan pengembangan makam Mbah Donopuro Pangeran Semende. Faktor yang melatarbelakangi adanya pengembangan terdapat faktor sosial budaya yakni budaya leluhur yang perlu dilestarikan, faktor ekonomi untuk meningkatkan kualitas hidup masyarakat, serta faktor agama yang merupakan cikal bakal pesantren Indonesia. kesimpulan yang dapat ditarik dari penelitian ini yakni perelitian ini memberikan hasil yang sangat baik, dilihat dari keterlibatan langsung pihak Pemerintah desa, ta’mir, dan juga masyarakat sekitar. Adanya pengembnagan ini dapat meningkatka pendapatan masyarakat yang berdagang disekitar obyek wisata.